Recent advances of trace elements in autoimmune thyroid disease - Li, Shanshan; Xu, Qian; Wang, Shengjun; Peng, Huiyong; Liu, Yingzhao (Frontiers in Immunology, 2025)
Autoimmune thyroid disease (AITD), which includes Graves’ disease and Hashimoto’s thyroiditis, poses a substantial global health burden due to its strong environmental influences. Among environmental factors, trace elements are increasingly recognized for their dual roles in regulating thyroid physiology and immune function. This narrative review synthesizes current evidence on the roles of key trace elements-iodine, selenium, vitamin D, zinc, iron, copper, and magnesium-in AITD pathogenesis. We detail their essential functions in thyroid hormone synthesis and metabolism, and critically examine how imbalances (deficiency or excess) can disrupt immune homeostasis, thereby promoting autoimmunity via mechanisms like oxidative stress, aberrant immune cell differentiation, and loss of self-tolerance. This review highlights complex dose-response relationships, such as the U-shaped curve for iodine, and the protective roles of selenium and vitamin D through antioxidant and immunomodulatory pathways. For other elements, including zinc, iron, copper, and magnesium, emerging associations with AITD have been identified, but the mechanistic understanding remains limited. We conclude that imbalances in trace elements are pivotal environmental triggers for AITD. Future research should prioritize elucidating molecular mechanisms, investigating interactions among elements, and conducting long-term interventional studies to translate these findings into precise nutritional strategies for AITD prevention and management.